AUTHENTICATION OF SPRAGUE DAWLEY RATS (RATTUS NORVEGICUS) FAT WITH GC-MS (GAS CHROMATOGRAPHY-MASS SPECTROMETRY) COMBINED WITH CHEMOMETRICS - GUNTARTI, ANY; NINGRUM, KARINA PRIMATYAS; GANDJAR, IBNU GHOLIB; SALAMAH, NINA (International Journal of Applied Pharmaceutics, 2021)
Objective: Misuse of rat meat as food worried people. Rat meat can come from research waste; one of the rats used in the research was the Sprague Dawley. Analysis of rat meat in food can be done using fat. The aim of this study was to authenticate rat fat with GC-MS combined with chemometrics. Methods: The meat of Sprague Dawley rats, wild boar, goats, cow, and processed meatballs was put in the oven at 90-100 °C for±one hour, then derivatized with BF3 and NaOH in methanol to get the methyl ester for injected in GC-MS instrument. The results obtained were in the form of chromatograms and spectrograms. The data was processed using Principal Component Analysis (PCA) to grouping rat's meat with others (wild boars, goats, cows, and processed meatballs). Results: Rat meat fatty acid analysis results with GC-MS were obtained oleate (43.32±1.43)%, linolenate (32.24±1.46)%, palmitate (19.75±0.09)%, palmitoleate (1.14±0.06)%, stearate (0.26±0.01)%, myristate(0.18±0.01)%, margarate (0.15±0.02)%, and pentadecanoate (0.14±0.01)%. The PCA chemometrics results showed that rat meats had scores that close to cows, which meant they had similar fatty acid composition. Conclusion: The GC-MS method, combined with PCA chemometrics, tested rat fat with other animals and processed meatballs samples on the market.